THE EFFECT OF PRONUNCIATION TRAINING ON ENGLISH SPEAKING SKILL AMONG ENGLISH NON-NATIVE SPEAKERS (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Speaking a foreign language requires various skills, including grammar, vocabulary, instruction, etc. In English Language Teaching, pronunciation is one of the most crucial abilities. If speakers have poor pronunciation, their words will be incomprehensible to audiences. Despite the difficulty of acquiring pronunciation, many EFL classrooms pay the least attention to pronunciation training. This study aims to evaluate the effect of pronunciation training on English speaking ability of non-non-native speakers. The method used is the Literature Review method. The results of the study show that pronunciation training has a positive effect on the English-speaking ability of non-non-native speakers. This training helps improve pronunciation, intonation, and accent in speaking English. Non-non-native speakers also experience increased confidence in speaking English after attending pronunciation training. However, the results of the study also show that factors such as difficulties in mastering vocabulary and grammar still affect the ability to speak English as a whole. Therefore, it is advisable to consider pronunciation training as part of a holistic and integrated English learning program with special attention to other aspects such as vocabulary and grammar.
Keywords: Pronunciation training; Speaking ability; Non-non-native speakers